2005
DOI: 10.1002/pssb.200540026
|View full text |Cite
|
Sign up to set email alerts
|

Structure, stability and electronic properties of TiO2 nanostructures

Abstract: PACS 61.46.+w, 71.15.Mb, The structural properties, the stability and the electronic properties of various nanostructures based on the titania layer modifications (anatase and lepidocrocite) are studied using the density-functional-based tightbinding method (DFTB). The anatase nanotubes were found as the most stable nanostructure of TiO 2 . Based on the results of the calculations of the anatase nanostructures a model of their stability was developed. All anatase nanoforms are semiconductors with a direct band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 56 publications
5
112
1
2
Order By: Relevance
“…We consider here three types of the nanotubes constructed from initial anatase slabs. The 3-layer model of the anatase (101) slab consists of three atomic layers (O-Ti-O), however, its structural optimization results in formation of fluorite-type (111) slab [17,19] in which the symmetry can be attributed to the layer group 72 (P3 1). It is the same for 3-layer slab with both anatase and fluorite structures, although the space symmetry of fluorite TiO 2 bulk crystal is described by cubic space group 225 (F 3 ).…”
Section: Symmetry Of Tio 2 Single-walled Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider here three types of the nanotubes constructed from initial anatase slabs. The 3-layer model of the anatase (101) slab consists of three atomic layers (O-Ti-O), however, its structural optimization results in formation of fluorite-type (111) slab [17,19] in which the symmetry can be attributed to the layer group 72 (P3 1). It is the same for 3-layer slab with both anatase and fluorite structures, although the space symmetry of fluorite TiO 2 bulk crystal is described by cubic space group 225 (F 3 ).…”
Section: Symmetry Of Tio 2 Single-walled Nanotubesmentioning
confidence: 99%
“…For 2D structure, a slab model of thermodynamically stable anatase TiO 2 (101) surface [1] was mainly applied, which can be easily organized in double sub-sheets consisting of the two formula units with sixlayer O-Ti-O_O-Ti-O structure with a centered rectangular morphology [13]. Nevertheless, the latter was very scarcely considered for simulation on TiO 2 NTs, during the last three years only [14][15][16], while a number of earlier and recent simulations on TiO 2 NTs were limited by triplelayered O-Ti-O structure, with optimization resulted in a hexagonal fluorite-like morphology [17][18][19][20][21]. This is not only due to computational limitations, , insufficient application of formalism of rotohelical symmetry in ab initio calculations, but also due to a presence of 3-layer fragments in structural units of separate walls in MW TiO 2 NTs [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As you know photo catalyst is a material that in light radiation resulted into chemical reaction but itself never changes and just provide proper conditions to perform a reaction [22,23]. Titanium dioxide is in the Nano metrical size of an ideal photo catalyst and the most important reason for the presence of this feature is the ability of absorbing ultra-violet rays [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…13 Structural, electronic and vibrational properties of titania chains embedded in ETS-10 have been studied using ab initio methods. 14 Moreover, Enyashin et al 15,16 have studied the stability and electronic structure of various TiO 2 nanotubes governed from anatase and lepidocricite layer modifications by using density-functional-based tightbinding method. Futhermore, ab initio calculations are reported that investigates atomic scale 17 as well as the rutile 18 TiO 2 nanowires.…”
Section: Introductionmentioning
confidence: 99%